Self-management-based health coaching for sustainable behavior change in chronic disease care: A concept analysis using Walker and Avant’s framework - Rian Adi Pamungkas; Kathlen Potempa; Kanittha Chamroonsawasdi; Andi Mayasari Usman; Samoraphop Banharak (Belitung Nursing Journal, 2026)
Background: Self-management-based health coaching is increasingly applied in chronic disease management; however, conceptual ambiguity persists regarding its defining characteristics and theoretical boundaries. A clear and consistent conceptualization is essential to strengthen its application in nursing research and practice. Objective: This study aimed to clarify the concept of self-management–based health coaching in chronic disease care. Method: A concept analysis was conducted using Walker and Avant’s framework. A systematic literature search was conducted across multiple databases (PubMed, ScienceDirect, and Google Scholar) for studies published between January 2000 and June 2025, resulting in 49 articles included in the analysis. Conceptual elements were extracted and synthesized using iterative content analysis and constant comparison. Results: The analysis identified seven core attributes (health-focused, partnership and collaboration, client-centered, goal-oriented, process-driven, enlightening, and empowering) that reflect a collaborative, client-centered, and process-oriented approach that facilitates insight and empowerment in behavior change. Antecedents included individual readiness and supportive contextual conditions, while consequences encompassed psychological, behavioral, and clinical outcomes. Model and additional cases further illustrated the concept’s application and boundaries. Conclusion: This study provides a clearer conceptual understanding of self-management–based health coaching and highlights its relevance for guiding theory-informed research and practice in chronic disease management. However, further empirical and theoretical work is needed to refine and validate the concept across diverse contexts.